2020
DOI: 10.1038/s41746-020-0286-7
|View full text |Cite
|
Sign up to set email alerts
|

A data-driven framework for selecting and validating digital health metrics: use-case in neurological sensorimotor impairments

Abstract: Digital health metrics promise to advance the understanding of impaired body functions, for example in neurological disorders. However, their clinical integration is challenged by an insufficient validation of the many existing and often abstract metrics. Here, we propose a data-driven framework to select and validate a clinically relevant core set of digital health metrics extracted from a technology-aided assessment. As an exemplary use-case, the framework is applied to the Virtual Peg Insertion Test (VPIT),… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
144
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(147 citation statements)
references
References 129 publications
(204 reference statements)
3
144
0
Order By: Relevance
“…No clear correlations were found between the kinematic metrics and the FMA-UE, whereas trunk compensation and elbow flexion/extension showed strong correlation with the FMA-UE arm subsection, as well as the correlation between the FMA-UE hand subsection and finger flexion/extension. These findings are in line with existing research [ 24 , 44 ] and support the fact that kinematic parameters are, rather, complementary than redundant to standard clinical scales and potentially add clinically relevant information. The large interquartile ranges in all measured DOF in all study subjects illustrates the large variability in movement execution especially in non-cyclical discrete motions.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…No clear correlations were found between the kinematic metrics and the FMA-UE, whereas trunk compensation and elbow flexion/extension showed strong correlation with the FMA-UE arm subsection, as well as the correlation between the FMA-UE hand subsection and finger flexion/extension. These findings are in line with existing research [ 24 , 44 ] and support the fact that kinematic parameters are, rather, complementary than redundant to standard clinical scales and potentially add clinically relevant information. The large interquartile ranges in all measured DOF in all study subjects illustrates the large variability in movement execution especially in non-cyclical discrete motions.…”
Section: Discussionsupporting
confidence: 91%
“…Being able to detect the main aspects of movement quality and impairments allows selecting and monitoring changes in functional outcome and planning interventions that target these aspects. Future research should consider and re-evaluate the outcome features and task considerations presented herein on larger sample sizes to further underpin existing evidence of sufficient validity and reliability for metrics of joint range of motion and trunk displacement [ 24 , 44 ]. Furthermore, analysis of the assessments’ clinimetric properties should be extended to domains sensitivity and specificity for differentiation physiological and pathological movement behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a core set of 10 kinematic and kinetic VPIT metrics was selected from a set of 77 candidate metrics based on an automated, data-driven metric selection process that optimizes clinically-relevant statistical criteria for longitudinally assessing impairments [ 32 ]. These metrics are extracted through an advanced processing and normalization pipeline that is applied to the position and grip force data from the VPIT, sampled at 1 kHz [ 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…The Virtual Peg Insertion Test (VPIT) addresses many of the limitations of existing technology-aided assessments by recording movement and grip force patterns during a virtual goal-directed manipulation task requiring coordinated arm and hand movements [ 31 , 32 ]. Previous research indicated the feasibility of the approach in neurologic individuals with mild to moderate sensorimotor impairments [ 32 – 35 ]. In addition, ten digital health metrics capturing sensorimotor impairments have been established for the VPIT and allowed for an accurate discrimination between neurologically intact and affected individuals [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation